Penerapan Metode CRT Untuk Memupuk Antusiasme Belajar Siswa Kelas Iv Dalam Materi Aktivitas Permainan SDN Pakis 1 Surabaya Tahun Pelajaran 2024/2025 - Ramadhan Ramadhan; Anung Priambodo; Marsudianto Marsudianto (Student Research Journal, 2024)
This study aims to enhance the learning enthusiasm of 4B grade students at SDN Pakis 1 Surabaya in Physical Education, Sports, and Health (PJOK) through the implementation of traditional games, specifically "gobak sodor," using a Culturally Responsive Teaching (CRT) approach. The method employed is Classroom Action Research (CAR) consisting of two cycles. Data were collected through questionnaires to measure student learning interest and direct observations during the learning process. Analysis results show an increase in student learning interest from 48.40% in the first cycle to 70.80% in the second cycle. The application of traditional games proved effective in creating a more enjoyable and interactive learning atmosphere while reinforcing cultural values. This research concludes that integrating traditional games into learning not only boosts student motivation but also provides a richer and more meaningful learning experience. Therefore, it is recommended to adopt similar approaches in other learning contexts.